2006
DOI: 10.1002/jnr.20970
|View full text |Cite
|
Sign up to set email alerts
|

PTEN, Akt, and GSK3β signalling in rat primary cortical neuronal cultures following tumor necrosis factor‐α and trans‐4‐hydroxy‐2‐nonenal treatments

Abstract: PTEN is a dual phosphatase that negatively regulates the phosphatidylinositol 3-kinase (PI3K)/Akt signalling pathway important for cell survival. We determined effects of the inflammation and oxidative stresses of tumor necrosis factor-alpha (TNFalpha) and trans-4-hydroxy-2-nonenal (HNE), respectively, on PTEN, Akt, and GSK3beta signalling in rat primary cortical neurons. The inhibitors bisperoxovanadium [bpV(Pic)] and LY294002 were also used to determine PTEN and PI3K involvement in TNFalpha and HNE modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
(39 reference statements)
1
8
0
Order By: Relevance
“…4-HNE can also be conjugated with GSH through Michael adduction 12. Results of our present study and of previous reports14,42,43 suggest that RPE cells use the Nrf2-dependent antioxidant system to detoxify 4-HNE.…”
Section: Discussionsupporting
confidence: 75%
“…4-HNE can also be conjugated with GSH through Michael adduction 12. Results of our present study and of previous reports14,42,43 suggest that RPE cells use the Nrf2-dependent antioxidant system to detoxify 4-HNE.…”
Section: Discussionsupporting
confidence: 75%
“…242 Consistently, HNE (5 mM) was found to induce early neuronal cell death. 243 On the contrary, using human neuroblastoma IRM-32 cells, Dozza et al 244 observed that treatment with 10 mM HNE provoked significant inhibition of the glycogen synthase kinase 3b, likely through the phosphorylation and activation of both Akt and ERK2; this HNEdependent effect was clearly abolished by cell co-treatment with LY294002 or U0126, inhibitors of the PI3K and ERK pathways, respectively. 244…”
Section: B Effect On the Serine/threonine Kinase Aktmentioning
confidence: 99%
“…It has been reported that PTEN protein levels are reduced in AD brains accompanied by elevated Akt phosphorylation [106, 107, 108]. It was recently shown that S -nitrosylation of PTEN was markedly elevated in the brains in the early stages of AD [87].…”
Section: Contribution Of No and Protein S-nitrosylation In The Bramentioning
confidence: 99%